A bearing bush with a composite lubricating structure and a slow-release control system thereof
Patent Information
- Application Number
- CN202611042470.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-05-25
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]发明目的:针对现有技术中轴瓦润滑剂释放被动、不可控,无法适应低速重载及变工况需求,导致润滑不良、早期磨损、轴瓦寿命短的问题,本发明的第一目的为提供一种提高轴瓦使用寿命的具有复合润滑结构的轴瓦;本发明的第二目的为实现对复合润滑结构的轴瓦的复合润滑体主动、精准、按需释放的缓释调控系统
[0052](1)本发明具有复合润滑结构的轴瓦通过在轴瓦的复合润滑体中引入电致体积变化材料聚苯胺,通过外部电信号控制,能够实现润滑剂平稳、持久、可控的“缓释”,显著延长了轴瓦服役寿命;
Smart Images

Figure CN122880832A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sliding bearing design, and specifically relates to a bearing bush with a composite lubrication structure and a method for controlling the slow release of lubrication in the bearing bush. Background Technology
[0002] In large rotating machinery, such as ship propulsion shafts and heavy rolling mills, bearings often operate under low-speed, heavy-load conditions, resulting in a mixed lubrication state. Under these conditions, an oil film is difficult to fully establish, and the bearing is supported by both the oil film and surface micro-protrusions, easily leading to abnormal wear and even serious failures such as "shaft seizure" or "bearing failure." Traditional lubrication methods rely on grease or circulating oil, with a continuous or quantitative supply of lubricant, making precise adjustment based on the wear state of the friction interface impossible. During the break-in period, wear is often exacerbated due to the lack of a boundary film and the contact of sharp, rough peaks.
[0003] In existing technologies, using surface microtextures to store solid lubricants is an effective means of improving tribological properties. However, some problems still exist. On the one hand, such structures usually rely on the mechanical or thermal effects during the friction process to passively release the lubricant. The release rate and timing are uncontrollable, and it is impossible to actively provide additional lubrication when needed. On the other hand, passive release often occurs too quickly in the initial stage and cannot be sustained in the later stage, making it impossible to achieve long-term, intelligent lubrication management, resulting in a short service life of the bearing. Summary of the Invention
[0004] Purpose of the invention: In view of the problems in the prior art where the release of lubricant in bearing bushes is passive and uncontrollable, unable to adapt to the needs of low speed heavy load and variable working conditions, resulting in poor lubrication, premature wear and short bearing bush life, the first purpose of the present invention is to provide a bearing bush with a composite lubrication structure to improve the service life of bearing bushes; the second purpose of the present invention is to realize a slow-release control system for the active, precise and on-demand release of the composite lubricant body of the bearing bush with a composite lubrication structure.
[0005] Technical Solution: The bearing bush with a composite lubrication structure of the present invention has a micro-textured array on the surface of the bearing area, the surface of the micro-textured array is filled with a composite lubricant, and then cured; the cured lubricant comprises, by weight, 40%~50% electro-volume change material, 30%~40% solid lubricant, and 20%~30% ultraviolet light curable resin; the electro-volume change material is polyaniline; the solid lubricant has an electrical conductivity of not less than 10 at 25 °C. 4 S / m.
[0006] To improve the dispersibility of the filler, a dispersant, such as polyethylene glycol or silane coupling agent, can be added at a rate of 0.5% to 1.0% of the total mass.
[0007] The electro-induced volume change material serves as an electro-induced deformation driving unit, which can undergo reversible volume expansion under electric field stimulation, ensuring the generation of sufficient electro-induced expansion driving force.
[0008] The preferred morphology of the electro-induced volume change material can be nanofibers, microspheres, or mesoporous structures to increase the specific surface area and improve the response speed.
[0009] Preferably, the polyaniline is a polyaniline doped with protic acids such as hydrochloric acid and camphor sulfonic acid.
[0010] The solid lubricant, as a functional unit of the friction interface, must provide effective lubrication and ensure the necessary conductivity of the composite.
[0011] Preferably, the solid lubricant is a conductive solid lubricant or a mixture of a conductive solid lubricant and a non-conductive solid lubricant; the conductive solid lubricant is graphite, graphene, carbon nanotubes, or conductive carbon black; the non-conductive solid lubricant is molybdenum disulfide, tungsten disulfide, boron nitride, or polytetrafluoroethylene powder.
[0012] Preferably, when the solid lubricating material is a mixture of conductive solid lubricant and non-conductive solid lubricant, metal nanowires are also added.
[0013] Solid lubricants must contain at least one conductive solid lubricant. Their role is not only to provide lubrication, but more importantly, to construct a three-dimensional continuous conductive network within the composite, ensuring uniform current distribution and achieving efficient, synchronized electro-expansion. Non-conductive solid lubricants can further optimize overall tribological properties. When a formulation contains a non-conductive solid lubricant, it is essential to ensure that the overall conductivity of the composite meets the requirements for effective electro-expansion by increasing the content of conductive solid lubricants (such as carbon nanotubes) or by adding additional metal nanowires (such as silver nanowires or copper nanowires).
[0014] As a structural molding and interface adhesion guarantee unit, the photocurable resin firmly combines the electro-volume change material and the solid lubricant material and fixes them to the inner wall of the microtexture, so as to ensure that the composite has sufficient molding density, cohesive strength and excellent adhesion to the texture wall.
[0015] Preferably, the UV-curable resin is acrylic acid, methacrylic acid, ethyl acrylate, or propyl acrylate. UV-curable resins containing carboxyl or methyl groups can bond with the ammonia nitrogen on polyaniline; acrylates containing hydroxyl or methyl groups can form hydrogen bonds with polyaniline.
[0016] Preferably, the distribution design of the microtexture array includes:
[0017] (1) Circumferential angle range: The vertical centerline of the bearing bush is taken as the 0° reference line. For a unidirectional rotating shaft, the bearing bush microtexture is mainly distributed in the area bearing the oil film pressure, with an angle range of -30° to +60°, of which the oil film convergence area (+ direction) on the side of rotation direction introduction is the key distribution area. For a bidirectional rotating shaft, the bearing bush microtexture is symmetrically distributed on both sides of the centerline, with a total angle range of -60° to +60°.
[0018] (2) Axial range: In order to avoid excessive loss of end lubricant and suppress uneven wear caused by edge stress concentration, the micro-texture array is not processed in an area of not less than 5 mm from both ends of the bearing. The micro-texture is only distributed in the central area between the unprocessed areas.
[0019] Preferably, (1) the design of the morphology and geometric parameters of the microtexture includes:
[0020] (3) The cross-sectional shape is a groove or pit. The texture of the groove includes, but is not limited to, a cross-hatching pattern, a unidirectional spiral, or a straight groove parallel to the axis; the shape of the pit includes a circle, a square, a rhombus, or other polygons.
[0021] (4) The depth (H) is related to the thickness (T) of the alloy layer on the surface of the bearing substrate, and is set as H = (1 / 5~1 / 4)T. This design aims to balance sufficient lubricant reserves with the load-bearing strength and fatigue life of the substrate alloy layer.
[0022] (5) Width or diameter (D) is designed to be between 10 μm and 500 μm, with a surface area ratio of 5% to 30%.
[0023] The method for preparing the bearing bush with a composite lubrication structure according to the present invention includes the following steps:
[0024] (1) Substrate pretreatment and microtexturing: The friction surface of the bearing substrate is cleaned and activated. According to the design parameters, the microtexturing array is precisely processed in the designated area using ultra-short pulse laser or micro-electro-discharge machining technology.
[0025] (2) Preparation of composite slurry: Weigh the electro-volume change material, solid lubricant, ultraviolet curable resin and other additives, mix with solvent, and disperse by ball milling or high-speed shearing to form a uniform, stable high-viscosity functional slurry;
[0026] (3) Slurry filling: The slurry is filled into the microtexture by scraping process to ensure complete filling and removal of air bubbles, and the surface is scraped smooth;
[0027] (4) Curing and molding: Curing is performed by irradiation with ultraviolet light;
[0028] (5) Surface finishing: The friction surface of the cured bearing bush is precision ground and polished to completely remove excess material on the surface, so that the surface of the composite lubricant and the original surface of the substrate are coplanar and flush.
[0029] Preferably, in step (2), the viscosity of the slurry should be controlled between 5000 and 20000 cP to ensure good leveling properties and filling fractal ability.
[0030] Preferably, in step (4), the curing process specifically includes: placing the filled bearing in an ultraviolet irradiation device, using a specific wavelength (315~400 nm) and sufficient light intensity (1000~1200 mW / cm²). 2 The slurry is subjected to full-area scanning irradiation with ultraviolet light for 10-60 seconds to ensure full photopolymerization and curing.
[0031] When irradiated with the above-mentioned ultraviolet (UV) parameters, polyaniline and photosensitive resin undergo a partial grafting reaction under UV irradiation, resulting in the following effects: increased interfacial compatibility between the photosensitive resin and polyaniline, preventing agglomeration; better entanglement of the grafted chains with the UV-curable resin, preventing rapid loss of the filler due to oil washout; and the polymer chains possess a certain degree of elasticity, acting as a buffer to prevent excessive expansion leading to filler breakage and improving the stability of the expansion-recovery cycle. After grafting, some active sites of polyaniline are occupied, reducing the anion storage capacity and affecting the volume expansion coefficient. Therefore, the above-mentioned UV parameters are preferred for reliable curing and partial grafting.
[0032] The bearing slow-release control system of the present invention includes the aforementioned bearing, power amplifier, signal generator, and PLC; an electrode is provided on the non-load-bearing area on the back of the bearing, and the electrode is connected to the positive terminal of the power amplifier; the crankshaft is connected to the negative terminal of the power amplifier via a slip ring; the power amplifier is connected to the signal generator, and the signal generator is connected to the PLC; a K-type thermocouple is embedded near the working surface of the bearing alloy layer, and the temperature measurement signal of the thermocouple is connected to the PLC controller; a lubricating oil containing anionic additives is used in the operation of the bearing.
[0033] The control method of the system includes the following steps:
[0034] (1) Break-in period: During the initial operation of the equipment, the control system starts at an initial frequency of 1000~2000Hz, and then the frequency ƒ decays with the cumulative operating time t according to the following formula:
[0035] f(t) = -kln(t) + b;
[0036] Where k is the attenuation coefficient and b is the frequency increment;
[0037] (2) Normal wear period: The bearing operating temperature is used as the feedback signal to implement closed-loop control, and the upper limit of the normal operating temperature T is set.max Real-time temperature monitoring T:
[0038] When T>1.2T max If the lubrication is severely insufficient, a pulse is applied at a first frequency n1 = 1000~1500 Hz for strong compensation.
[0039] If T max <T≤1.2T max If the condition is found to be slightly insufficient, a pulse is applied at n2=1~10 Hz to preventatively replenish the lubrication.
[0040] If T≤ max If the lubrication condition is good, the pulse output is cut off, and the system enters a zero-power standby state.
[0041] Where T max The temperature range is 70~90℃ (determined by the high temperature resistance (i.e., melting point) of the bearing alloy layer material, and is lower than the melting point of the alloy layer).
[0042] (3) Depletion period: When the solid lubricant in the composite lubricant has been basically depleted, the electrical signal output stops.
[0043] When the following conditions are met simultaneously: a) the bearing bush has completed its break-in period; b) the shaft supported by the bearing bush has been running continuously for more than one hour since the start-up, passing the equipment start-up temperature rise phase; and c) after 10 minutes of output pulse voltage, the bearing bush temperature continues to rise without decreasing the rate of temperature rise, it can be considered that the solid lubricant has been depleted, and the electrical signal output should be stopped at this point. During this stage, the microtextured structure remains on the bearing bush surface, and its geometric pit structure can continue to serve as a lubricant storage space and abrasive grain containment space, maintaining lubricant supply to a certain extent and reducing abrasive damage to the friction pair, thereby providing auxiliary improvement to the bearing's friction performance. The solid lubricant depletion time can be determined through friction testing.
[0044] Due to variations in the mass fraction of polyaniline and break-in conditions, different release rates can be obtained at the same frequency. The release rate is also affected by the break-in load and speed. Adjusting the frequency, and based on the actual break-in load, speed, and lubricating oil flow rate, a 30-minute friction test was conducted to determine the release rate (by dividing the height difference of the filling material within the texture at the initial stage and after the test by time; height was measured using a laser 3D profilometer or contour approximation device). This yielded the relationship between the release rate and frequency. Following the optimal release rate curve, release rates at 30 min, 60 min, 90 min, and 120 min were measured. Based on the relationship between release rate and frequency, the corresponding pulse frequencies were obtained, leading to the coordinates (t1, f1), (t2, f2), (t3, f3), and (t4, f4). These coordinates were then fitted to obtain k and b in the frequency attenuation formula. The optimal release rate curve (the relationship between release rate and time) has been obtained through numerous experiments, and multiple coordinate points for frequency and time were obtained from these two relationships. These points were then fitted.
[0045] During the break-in period, the frequency ƒ automatically and smoothly decreases according to a preset formula. When the fluctuation range (or rate of change) of the friction coefficient and friction vibration amplitude is less than 10% within a continuous 30-minute time window, and this state lasts for more than 10 minutes, the break-in period is determined to be over, and the system automatically switches to the control mode of the normal wear period.
[0046] Preferably, the power amplifier uses low-voltage pulsed DC power, with the operating voltage set between +0.2 and +0.6 V. Within this voltage range, polyaniline is in an intermediate oxidation state and exhibits high conductivity.
[0047] Preferably, the pulse frequency of the signal generator is set to 5 Hz to 1500 Hz, and the duty cycle of a single pulse is set to 10% to 30%. This "work-intermittent" mode allows the ion migration process to be periodically paused, thereby achieving a smooth and slow release, reducing Joule heat accumulation, and extending material life. If the pulse frequency is too low, the slow-release effect is weak; if the pulse frequency is too high, it can easily lead to instantaneous excessive expansion of the polyaniline phase, which may cause composite cracking and a one-time burst release of lubricant.
[0048] Preferably, the lubricating oil of the anionic additive is sodium petroleum sulfonate, alkyl phosphate salt, or ionic liquid. The anions dissociated from these additives can serve as an external ion source, participating in and maintaining the electrochemical expansion reaction of polyaniline.
[0049] Invention Mechanism:
[0050] This invention involves filling the surface of a microtextured array of bearing bushes with a composite lubricant comprising an electro-volume change material, a solid lubricant, and a UV-curable resin. The bearing bushes are then integrated into a slow-release control system. When a voltage is applied, the electro-volume change material, polyaniline, undergoes an electrochemical oxidation reaction under a positive voltage. Nitrogen atoms in the molecular chains oxidize and acquire a positive charge. To maintain electroneutrality, anions are inserted into the matrix. Diesel engine lubricating oil contains abundant anionic additives. The insertion of anions increases the distance between molecular chains, resulting in a macroscopic volume expansion effect. The voltage magnitude and the number of pulses affect the number of anions inserted, thus influencing the degree of volume expansion. The expanded polyaniline and other solid lubricants in the texture are carried into the friction interface under the action of friction, providing lubrication.
[0051] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0052] (1) The bearing bush with composite lubrication structure of the present invention introduces polyaniline, an electro-volume change material, into the composite lubricant body of the bearing bush. Through external electrical signal control, it can achieve stable, long-lasting and controllable "slow release" of lubricant, which significantly extends the service life of the bearing bush.
[0053] (2) Compared with similar composite lubrication bearings without active slow-release function, the bearings with composite lubrication structure of the present invention can effectively extend the service life and significantly reduce the abnormal wear loss efficiency during the break-in period.
[0054] (3) The bearing slow release control system of the present invention realizes the fundamental transformation of lubricant from "passive slow release" to "active intelligent on-demand supply". Compared with the traditional passive release bearing, the present invention can accurately respond to changes in working conditions such as start-up, load change and abnormal temperature rise through electrical signals and adjust the lubricant release rate in real time.
[0055] (4) Under simulated low-speed heavy-load conditions, the peak friction coefficient of the bearing bush using the present invention can be reduced by more than 40% during the start-up phase, and the lubrication response delay during sudden changes in working conditions is less than 100 milliseconds, which greatly improves the active adaptability of lubrication and the effectiveness of protection.
[0056] (5) The forced construction of a continuous conductive network within the composite significantly improves the response efficiency and reliability of electro-induced expansion. By forcibly introducing conductive solid lubricants such as graphene and carbon nanotubes into the composite lubricant and forming a three-dimensional continuous network, this invention solves the problem of uneven electric field caused by traditional insulating lubricant filling. Compared with the control sample that only uses polyaniline without constructing a conductive network, the response uniformity of electro-induced expansion is significantly improved, and the effective expansion volume under the same electrical parameters is greatly increased, thereby ensuring the consistency and reliability of intelligent control. Attached Figure Description
[0057] Figure 1 This is a flowchart illustrating the fabrication process of the bearing bush with a composite lubrication structure according to the present invention.
[0058] Figure 2 A schematic diagram of the surface texture processing of the bearing bush;
[0059] Figure 3 Schematic diagram of filling microtextured pits with material;
[0060] Figure 4 This is a schematic diagram of the connection of the bearing slow-release control system of the present invention;
[0061] Figure 5 This is a flowchart of the control method of the bearing slow-release control system of the present invention;
[0062] Figure 6 This is a flowchart of the control method of the bearing slow-release control system of the present invention;
[0063] Figure 7 This is a graph showing the bearing release rate of Embodiment 2 of the present invention;
[0064] Figure 8 This is a comparison chart of the surface friction coefficients of the bearing bush with the slow-release control system in Embodiment 3 of the present invention and that of a traditional bearing bush;
[0065] Figure 9 This is a comparison chart of the wear amount of the bearing bush with the slow-release control system in Embodiment 3 of the present invention and that of a traditional bearing bush;
[0066] Figure 10 This is a diagram showing the surface texture of the bearing bush in Embodiment 3 of the present invention, which includes a slow-release control system, compared to that of a traditional bearing bush. Detailed Implementation
[0067] The technical solution of the present invention will be further described below with reference to the embodiments.
[0068] Example 1
[0069] The bearing bush with a composite lubrication structure described in this invention is prepared by the following steps:
[0070] Step 1: Preparation of microtexture on bearing surface
[0071] (1) Planning and preparation of microtextured areas of bearing bush
[0072] The bearing is a composite lubricating bearing for marine diesel engines. It has a semi-cylindrical structure with an inner diameter of about 200 mm, an axial width of about 100 mm, an alloy layer thickness of about 140 μm, and a surface alloy layer of tin-based Babbitt alloy.
[0073] like Figure 2As shown, the microtextured processing area is a sector-shaped region ranging from -60° to +60° axially, with the vertical center line (0° line) as the reference. Axially, the processing area is defined by a boundary 12 mm from each end face of the bearing. The cleaned bearing substrate is fixed on a high-precision CNC rotary table for positioning during subsequent laser processing.
[0074] (2) Determine the microtexture shape and unit parameters
[0075] The microtexture is an array of circular pits, with a diameter D = 80 μm and a depth H = 35 μm (approximately 1 / 4 of the thickness T of the Babbitt alloy layer, T ≈ 140 μm) for each pit. The center-to-center distance of the pits is P = 150 μm, and the theoretical area occupancy is approximately 22%.
[0076] (3) Microtexture processing: A picosecond laser processing system is used to scan and ablate within a planned area to precisely process the circular pit array described in step (2).
[0077] Step 2: Prepare the composite lubricating slurry, specifically as follows:
[0078] (1) Determine the material formulation: by mass ratio: polyaniline (PANI, conductivity at 25 ℃ 5~10 S / cm): graphene nanosheets (conductivity at 25 ℃ 6× 10 S / cm) 6 S / m: Photocurable resin (66% epoxy acrylate of type 621A-80, 3% photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, 31% 1,6-hexanediol and acrylate) = 5:3:2; 0.8% polyethylene glycol-400 is added as a dispersant.
[0079] (2) Slurry preparation process: Weigh the raw materials accurately according to the above proportions. First, place 125 g of PANI nanofibers, 75 g of graphene nanosheets and 2 g of dispersant polyethylene glycol-400 in a planetary ball mill jar, add 200 mL of N-methylpyrrolidone solvent, and ball mill at 300 rpm for 0.5 hours to obtain a uniformly dispersed conductive slurry. Then add 50 g of photocurable resin and continue ball milling for 0.5 hours to form a uniform black composite slurry with a viscosity of approximately 12000 cP.
[0080] Step 3: Filling and curing the composite lubricant, specifically:
[0081] (1) Precision filling of slurry: The slurry is filled into the microtexture using a scraping process to ensure complete filling and expel air bubbles, and the surface is smoothed (e.g. Figure 3 (As shown).
[0082] (2) Solvent evaporation and photocuring: The filled bearing was placed in a vacuum drying oven and treated at 60°C for 2 hours to completely remove the solvent. The filling slurry was then photocured. Ultraviolet light with a wavelength of 365 nm was used at 1100 mW / cm². 2 Under light intensity of 500 mW / cm², the entire surface of the bearing was scanned and irradiated for 40 seconds. 2 Uncured; 800 mW / cm 2 Hardness after curing: 38.51 HV; 1000 mW / cm 2 Hardness after curing: 96 HV; 1200 mW / cm 2 The hardness after curing is 98 HV. Ultraviolet light initiates a photopolymerization reaction in the photosensitive resin, causing the slurry to cure rapidly at room temperature, forming a dense composite lubricant.
[0083] (3) Precision grinding of the surface: The inner surface of the cured bearing bush is precision ground and polished using a method from W 40 To W 1.5 The diamond polishing paste is gradually refined until the surface of the composite lubricant is completely flush with the surrounding Babbitt metal surface.
[0084] Example 2
[0085] like Figure 4 As shown in Figure 5, the bearing slow-release control system of the present invention includes a bearing with a composite lubrication structure prepared in Example 1, a power amplifier, a signal generator, and a PLC; an electrode is provided on the non-load-bearing area on the back of the bearing, and the electrode is connected to the positive terminal of the power amplifier; the crankshaft is connected to the negative terminal of the power amplifier via a slip ring; the power amplifier is connected to the signal generator, and the signal generator is connected to the PLC; a K-type thermocouple is embedded near the working surface of the bearing alloy layer, and the temperature measurement signal of the thermocouple is connected to the PLC controller; a lubricating oil containing anionic additives is used in the operation of the bearing.
[0086] The preparation method includes the following steps:
[0087] Step 1: Integrating embedded electrodes on the bearing surface, specifically:
[0088] (1) A micro blind hole is machined in the non-load-bearing area on the back of the bearing bush, and a gold-plated copper electrode rod with a diameter of 0.5 mm is pressed in and fixed.
[0089] (2) Construct an intelligent sustained-release regulation system, specifically as follows:
[0090] Hardware System Setup: The prepared bearing bush is installed on the test bench, with the two electrodes on the back of the bearing bush connected to a programmable pulse power supply. The bearing bush is connected to the positive terminal, and the crankshaft is connected to the negative terminal via a slip ring. The prepared bearing bush is installed on the test bench frame. Electrode rods are inserted into the non-load-bearing area on the back of the bearing bush and connected to the positive output terminal of the programmable pulse power amplifier via shielded cables. A mercury slip ring is installed at the shaft end, with the rotor end of the slip ring reliably connected to the shaft and the stator end connected to the negative output terminal of the power amplifier, thus forming a complete current loop. A K-type thermocouple is embedded near the working surface of the bearing bush alloy layer for real-time temperature monitoring, and the signal is input to the PLC controller. The power amplifier is connected to a signal generator, which is in turn connected to the PLC controller. The PLC runs a control algorithm based on the temperature signal collected by the thermocouple and sends control signals to the signal generator through its analog output module, setting the pulse frequency and duty cycle in real time. The signal generator generates a corresponding low-voltage pulse waveform, which is transmitted to the power amplifier for power amplification and then applied to the bearing bush through the loop formed by the electrodes and slip ring, forming a complete closed-loop control system.
[0091] Step 2, the control method of the system ( Figure 6 ), including the following steps:
[0092] Control strategy parameter setting: The parameter setting of the control strategy is implemented in the PLC through programming to realize the three-stage control logic. First, in the basic electrical parameters, the pulse waveform is a square wave, the voltage is set to 0.4 V, the target current density is 2.5 mA / cm², and the duty cycle is fixed at 20%.
[0093] Break-in period: Set the initial frequency f initial =1500 Hz. After running, the pulse frequency is automatically adjusted according to the formula ƒ(t)= -0.3ln(t)+5, where t is the running time (min).
[0094] Due to different load and speed conditions, different release rates can be obtained at the same frequency. The release rate is also affected by load and speed. Adjusting the frequency, and according to the actual load, speed, and lubricating oil flow rate, a 30-minute friction test was conducted to determine the release rate (measured by dividing the height difference of the filling material in the texture at the initial stage and after the test by time. Height was determined using a laser 3D profilometer or contour meter). The relationship between release rate and frequency was obtained. Based on the optimal release rate curve (r = -0.908ln(t) + 5.1207, i.e., the relationship between release rate and time), release rates of 2.1, 1.4, 0.9, 0.7, 0.6, and 0.52 were taken at 30 min, 60 min, 90 min, and 120 min, respectively (e.g., ...). Figure 7), according to the relationship between the release rate and frequency, the corresponding pulse frequency is obtained, and then the coordinates (30, 3.98), (60, 3.77), (90, 3.65), (120, 3.56) are obtained. Through fitting, k=0.3 and b=5 in the frequency attenuation formula are obtained. Normal wear period: set the temperature threshold T max =85°C. The alloy layer on the surface of the bearing bush is tin-based Babbitt alloy with a melting point of about 240°C, T max is valued based on the following: this value is within the allowable continuous working temperature range of tin-based Babbitt alloy (usually 70~120°C), under which the alloy layer can maintain sufficient hardness and compressive strength to avoid softening and deformation; at the same time, a safety margin is reserved for sudden temperature rise (1.2 times Tmax=102°C, which is still lower than the upper limit of allowable working temperature), and the stability of the lubricant and the energy consumption economy of the system are both taken into account. If the monitored temperature T>89.25°C (that is, 1.05 times Tmax, used as the early warning threshold), the system automatically continuously outputs pulses at a frequency of 1200Hz; if 85°C<T≤89.25°C, the system outputs pulses intermittently at a frequency of 5 Hz (works for 10 minutes and stops for 50 minutes); if T≤85°C, the system turns off the pulse output and enters a zero-power standby state.
[0095] Depletion period: when the following 3 conditions are simultaneously met, it is considered that the solid lubricant is exhausted: a. the bearing bush has completed run-in; b. after the current startup of the shaft supported by the bearing bush, it has been continuously operated for more than 1 hour, passing through the temperature rise stage during equipment startup; c. after outputting the pulse voltage for 10 minutes, the temperature of the bearing bush continues to rise and the temperature rise rate does not decrease. The system locks and stops output, only retaining the temperature monitoring function.
[0096] In the test, SAE 40 CD grade diesel engine oil containing 1.0 wt% sodium petroleum sulfonate was used as the lubricating medium to provide a continuous source of anions for the electrochemical expansion of polyaniline.
[0097] Test for release rate of solid lubricant:
[0098] Under specific electronic control parameters, square wave pulses are adopted, with a voltage of +0.4 V, a duty cycle of 20%, and a pulse frequency of 1000 Hz, and a test curve of the release rate of solid lubricant in the composite lubricant changing with time is drawn. In the test, a continuous pulse electrical signal is applied to the bearing bush sample integrated with the intelligent composite lubricant. After the end of each energization pulse and during the power-off recovery stage (that is, after the polyaniline phase contracts), a white light interferometer is immediately used to accurately measure the surface profile of the composite lubricant in the micro-texture, and its average depth consumption is calculated. The release rate (unit: μm / min) is calculated by the following formula:
[0099]
[0100] Where: v is the average release rate, h0 is the initial average depth of the composite lubricant before energization, and h t is the average depth of the composite lubricant after energization and de-energization, and t is the effective duration of a single energization. The results are as follows: Figure 7 As shown.
[0101] Depend on Figure 7 It can be seen that the release rate of the solid lubricant in the composite lubricant shows a gradual decreasing and stabilizing trend over time. In the initial stage of the experiment (30 min), the release rate was approximately 2.1 μm / min. At this time, under the action of the pulsed electrical signal, the conductive polyaniline underwent a volume change, driving the rapid release of the lubricant within the microtexture. As time increased, the release rate gradually decreased, leveling off within the 120–180 min range and stabilizing at around 0.52–0.7 μm / min, indicating that the system entered a stable, slow-release phase. This result demonstrates that the composite lubricant of the present invention can achieve continuous and controllable release of the solid lubricant under the action of an electrical signal, thereby helping to maintain a stable lubrication state at the friction interface.
[0102] Example 3
[0103] To verify the friction-reducing and wear-resistant performance of the bearing bush with composite lubrication structure described in this invention under different current excitation conditions, the composite lubrication structure sample prepared in Example 1 was installed in a friction and wear testing device for comparative testing, and the bearing bush slow-release control system prepared in Example 2 was used in the application. All samples used the same friction pair material (copper disc), lubrication conditions (copper disc surface uniformly covered with 0.5 mm thick base oil), rotation speed (500 r / min), test duration (35 min), and 13N normal load, with a sampling frequency of 200 Hz. The 13N group was the control group without current application, the 13N1A group was the low-current excitation group with 1A current application, and the 13N2A group was the high-current excitation group with 2A current application.
[0104] During the experiment, the frictional force of each group of samples was collected in real time, and the coefficient of friction was calculated. After the experiment, an electronic balance was used to measure the mass change of the samples before and after friction, and the wear was characterized by the mass difference before and after the experiment. Each group of experiments was repeated to ensure the comparability of the results. The test results are as follows: Figure 8 As shown.
[0105] Depend on Figure 8The friction coefficient of the 13N group without applied current was generally between 0.15 and 0.20, showing an increasing trend with the extension of test time. This indicates that under continuous friction, the lubricating film at the friction interface is gradually damaged, and the contact and adhesive wear of local micro-protrusions are enhanced. The friction coefficient of the 13N1A group after applying 1A current was generally between 0.14 and 0.18, lower than the control group without current, and the friction process was relatively stable. Statistical calculation of the friction coefficient throughout the test showed that the average friction coefficient of the 13N1A group was approximately 6.05% lower than that of the 13N group. These results indicate that under appropriate current, polyaniline in the composite lubricant can produce a relatively mild electroinduced volume response, driving the solid lubricating components such as graphene within the microtexture to gradually migrate to the friction interface. Simultaneously, the solid lubricating material can form a lubricating film with a certain load-bearing capacity and shear drag reduction effect on the contact surface, thereby reducing the direct contact area of the friction pair surface and lowering the interfacial shear resistance. When the applied current increased to 2A, the friction coefficient of the 13N2A group increased significantly, generally ranging from 0.18 to 0.37. Initially, its friction coefficient was similar to the other two groups; however, after approximately 16 minutes, the friction coefficient rapidly increased to over 0.30, exhibiting significant periodic fluctuations, with local peak values exceeding 0.35. Combining the sudden increase in friction coefficient with subsequent mass loss results, it can be concluded that under 2A current conditions, the local current density in the contact area of the friction pair significantly increases, easily leading to strong arc corrosion at the actual contact micro-protrusions. Higher currents passing through the friction contact area exacerbate local electrochemical reactions and Joule heating effects, causing damage to the surface oxide film or boundary lubrication film, and forming corrosion products, pits, and flaking particles in localized areas. These corrosion products and wear particles are repeatedly compacted, broken, and sheared during subsequent friction, forming an unstable third layer. This transforms the friction interface from a relatively stable boundary lubrication state to a corrosion-wear coupling state, resulting in a significant increase and large fluctuations in the friction coefficient.
[0106] like Figure 9 As shown, the mass changes of each group of samples before and after friction further reflect the wear differences under different current conditions. The mass loss of the 13N group samples was 0.011 g; the mass loss of the 13N1A group samples was 0.008 g, which is about 27.3% lower than that of the un-energized 13N group. Figure 8The result of a 6.05% reduction in the average friction coefficient indicates that a 1 A current can promote the stable and slow release of lubricating components from the composite lubricant without inducing significant electro-corrosion, thereby simultaneously improving both the friction coefficient and material loss. The mass loss of the 13N2A group was 0.018 g, an increase of approximately 63.6% compared to the 13N group and approximately 125% compared to the 13N1A group. This result shows that when the current increases to 2 A, electro-corrosion becomes the main factor affecting the service performance of the friction pair. Although higher currents may enhance the electro-responsiveness of polyaniline, the resulting localized corrosion, film damage, and material spalling effects outweigh the friction-reducing compensation effect of the composite lubricant, ultimately leading to a significant increase in both the friction coefficient and wear.
[0107] like Figure 10 As shown, after the same friction time, the un-energized 13N group still retained a large amount of continuous, dense black composite lubricant in the textured pits, indicating that this group mainly relied on passive release through frictional shear, and the release of solid lubricant was relatively limited. The 13N1A texture showed a significant reduction in the filled composite lubricant, with most of the pit bottom and edge areas exposed, leaving only a small amount of residual filler. This indicates that under 1A current stimulation, polyaniline underwent relatively sufficient and stable volume expansion, continuously pushing the solid lubricant components within the texture outwards and into the friction interface. The original continuous filling layer in the textured pits of the 2A current group essentially disappeared, and the texture interior was in a near-depleted state, indicating that higher currents could further enhance the volume response of polyaniline, causing rapid and large-scale release of solid lubricant components within the composite lubricant. However, combined with… Figure 8 and Figure 9 The results show that the rapid release of the composite lubricant in this group is accompanied by obvious current corrosion and material spalling, which is a non-ideal over-release state and is not conducive to the long-term stable service of the friction pair.
[0108] Depend on Figures 8 to 10 It is understood that the slow-release control system of this invention can utilize the volume expansion effect of polyaniline under the action of an electrical signal to regulate the release degree of the composite lubricant within the texture, realizing the transformation from passive release to active release. The greater the current intensity, the higher the release degree of the composite lubricant within the texture; however, when the current is too high, it is easy to cause current corrosion and interface instability, resulting in a significant increase in the friction coefficient and mass loss. Therefore, in actual operation, the slow-release control system of this invention should perform closed-loop regulation of the output current, pulse frequency, and duty cycle according to the bearing temperature, friction coefficient, vibration signal, and load changes, so as to keep the electro-induced volume change material within a controllable response range, avoid current corrosion caused by excessive current, and thus achieve stable release of the composite lubricant and continuous improvement of the tribological performance of the bearing.
Claims
1. A bearing bush with a composite lubrication structure, characterized in that, The bearing bearing has a microtextured array on its bearing area surface, which is filled with a composite lubricant and then cured. The cured lubricant comprises, by weight, 40%–50% electro-volume change material, 30%–40% solid lubricant, and 20%–30% UV-curable resin. The electro-volume change material is polyaniline. The solid lubricant has a conductivity of not less than 10 at 25 °C. 4 S / m.
2. The bearing bush with a composite lubrication structure according to claim 1, characterized in that, The polyaniline is a polyaniline doped with protic acids such as hydrochloric acid and camphor sulfonic acid.
3. The bearing bush with a composite lubrication structure according to claim 1, characterized in that, The solid lubricant is a conductive solid lubricant or a mixture of a conductive solid lubricant and a non-conductive solid lubricant; the conductive solid lubricant is graphite, graphene, carbon nanotubes or conductive carbon black; the non-conductive solid lubricant is molybdenum disulfide, tungsten disulfide, boron nitride or polytetrafluoroethylene powder.
4. The bearing bush with a composite lubrication structure according to claim 3, characterized in that, When the solid lubricating material is a mixture of conductive and non-conductive solid lubricants, metal nanowires are also added.
5. The bearing bush with a composite lubrication structure according to claim 1, characterized in that, The ultraviolet-curable resin is acrylic acid, methacrylic acid, ethyl acrylate, or propyl acrylate.
6. A bearing slow-release control system, characterized in that, The bearing includes a composite lubrication structure as described in any one of claims 1 to 5, a power amplifier, a signal generator, and a PLC; an electrode is provided on the non-load-bearing area on the back of the bearing, and the electrode is connected to the positive terminal of the power amplifier; the crankshaft is connected to the negative terminal of the power amplifier via a slip ring; the power amplifier is connected to the signal generator, and the signal generator is connected to the PLC; a K-type thermocouple is embedded near the working surface of the bearing alloy layer, and the temperature measurement signal of the thermocouple is connected to the PLC controller; a lubricating oil containing anionic additives is used in the operation of the bearing.
7. The bearing slow-release control system according to claim 6, characterized in that, The control method of the system includes the following steps: (1) Break-in period: During the initial operation of the equipment, the control system starts at 1000~2000Hz, and then the frequency ƒ decreases with the cumulative operating time t according to the following formula: f(t) = -kln(t) + b; Where k is the attenuation coefficient and b is the frequency increment; (2) Normal wear period: The bearing operating temperature is used as the feedback signal to implement closed-loop control, and the upper limit of the normal operating temperature T is set. max Real-time monitoring of temperature T When T>1.2T max If the lubrication is severely insufficient, a pulse is applied at a first frequency n1 = 1000~1500 Hz for strong compensation. If T max <T≤1.2T max If a slight lubrication deficiency is detected, a pulse is applied at a second frequency n2 = 1~10 Hz to preventatively replenish the lubrication. If T≤T max If the lubrication condition is good, the pulse output is cut off, and the system enters a zero-power standby state. Where T max The temperature is 70~90℃; (3) Depletion period: When the solid lubricant in the composite lubricant has been basically depleted, the electrical signal output stops.
8. The slow-release control system according to claim 6, characterized in that, The power amplifier uses low-voltage pulsed DC power, with the operating voltage set between +0.2 and +0.6 V.
9. The slow-release control system according to claim 6, characterized in that, The pulse frequency of the signal generator is set to 5 Hz to 1500 Hz, and the duty cycle of a single pulse is set to 10% to 30%.
10. The slow-release control system according to claim 6, characterized in that, The lubricating oil for the anionic additive is sodium petroleum sulfonate, alkyl phosphate salt, or ionic liquid.